Agricultural Crops Grown in Laboratory Conditions on Chernevaya Taiga Soil Demonstrate Unique Composition of the Rhizosphere Microbiota - Irina Kravchenko; Mikhail Rayko; Ekaterina Tikhonova; Aleksey Konopkin; Evgeny Abakumov; Alla Lapidus (Microorganisms, 2022)
Chernevaya taiga in West Siberia is a unique environment, with gigantism of grasses and shrubs. Exceptionally high productivity of plants is determined by the synergistic interaction of various factors, with a special role belonging to microorganisms colonizing the plant roots. This research explored whether agricultural plants can recruit specific microorganisms from within virgin Chernevaya Umbrisol and thus increase their productivity. Radish and wheat plants were grown on the Umbrisol (T1) and control Retisol of Scotch pine forest stand (T3) soils in the phytotron, and then a bacterial community analysis of the rhizosphere was performed using high-throughput sequencing of the 16S rRNA genes. In laboratory experiments, the plant physiological parameters were significantly higher when growing on the Umbrisol as compared to the Retisol. Bacterial diversity in T1 soil was considerably higher than in the control sample, and the principal coordinate analysis demonstrated apparent differences in the bacterial communities associated with the plants. Agricultural plants growing in the T1 soil form specific prokaryotic communities, with dominant genera Chthoniobacter, Pseudomonas, Burkholderia, and Massilia. These communities also include less abundant but essential for plant growth nitrifiers Cand. Nitrosocosmius and Nitrospira, and representatives of Proteobacteria, Bacilli, and Actinobacteria, known to be gibberellin-producers.